Virtual Reality Technology and Tourist Behavior Intention of National Museums in Guangdong - Yi Fei, Li (Universiti Malaysia Sarawak, 2024)
This study investigates the integration of virtual reality (VR)in museum exhibitions, focusing on its current development in museums within China's Guangdong region. It examines museum visitors'behavioural intentions towards VR, considering generational differences, and draws on the UTAUT2 model to formulate a conceptual framework. The research employs a specifically designed questionnaire for quantitative analysis in two phases. Initially, the PLS-SEM method identifies the primary factors influencing visitors' intentions. Subsequently, one-way ANOVA examines generational differences in these factors. The study finds performance expectancy, effort expectancy, social influence, design quality, hedonic motivation, and previous experience positively affect behavioural intentions, while perceived risk negatively influences them. Notably, generational differences are observed in effort expectancy, design quality, hedonic motivation, and perceived risk. Based on these insights, the study proposes targeted measures to improve VR acceptance among museum visitors in Guangdong, offering valuable references for similar research in the museum field.